202k views
0 votes

2 * - 3 = 4.5
how can l do this ​

User Grigoriy
by
4.5k points

1 Answer

3 votes

Simplifying

2x + -3 = 4.5

Reorder the terms:

-3 + 2x = 4.5

Solving

-3 + 2x = 4.5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.

-3 + 3 + 2x = 4.5 + 3

Combine like terms: -3 + 3 = 0

0 + 2x = 4.5 + 3

2x = 4.5 + 3

Combine like terms: 4.5 + 3 = 7.5

2x = 7.5

Divide each side by '2'.

x = 3.75

Simplifying

x = 3.75

User Swbbl
by
4.8k points